The role of prefrontal-hippocampal functional connectivity in schizophrenia-related cognitive dysfunction and the thalamic ventral midline involvement: in vivo and silico evidence - Černousova, Anastasija; Patrono, Enrico (Frontiers in Neuroscience, 2025)
Schizophrenia (SCZ) is a multiform psychiatric disorder in which impairments of high-order cognitive abilities, such as flexibility, working memory, and decision-making, are considered onset markers. These deficits are associated with dysfunctions in the prefrontal cortex (PFC) and hippocampus (HPC), two brain regions that play crucial roles in higher-order cognitive processes. While the roles of the PFC and HPC in SCZ have been widely studied, the interaction between these regions and their contributions to the observed cognitive deficits, in conjunction with other intermediate structures, refMRI connectivity as a biomarker main poorly understood. This paper primarily aims to create a hypothesis-generating framework in the context of PFC-HPC altered communication and intermediate structures that may contribute to cognitive impairments in psychosis-related conditions. Here, we present several testable hypotheses concerning the role of specific actors (e.g., GABAergic Parvalbumin-positive interneurons, thalamic calcium signaling channels) in the PFC-HPC connectivity. By presenting evidence from in vivo (animal models and human studies) and in silico studies (examining functional connectivity), we desire to reach computational and translational researchers, with the aim of stimulating further planning for new experimental methodologies, both computational and translational, that can provide a broad framework for a more nuanced understanding of maladaptive brain communication in psychosis.